Metal Oxides as Soluble Nano Catalyst on Biodiesel: A Review - Setyo Pambudi; Agus Triono; Mochamad Asrofi; Iid Mufaidah; Yeni Variyana; R. A. Ilyas (Journal of Applied Agricultural Science and Technology, 2021)
Nano particles of metal oxide developed as soluble nano additive in liquid fuels to improve fuel quality. One application of nano metal oxide particles is an additive to biodiesel. Biodiesel is an alternative fuel that can reduce dependence on fossil fuels. Pure biodiesel has a relatively lower calorific value compared to fossil fuels. Low calorific value results in increased brake specific fuel consumption. Moreover, biodiesel has a higher density and viscosity compared to fossil fuel. The content of carbon monoxide (CO), unburned hydrocarbons (HC) and nitrogen oxide (NOx) in exhaust gases with biodiesel is higher than fossil fuels. Metal oxide nanoparticles are added to biodiesel between 6 to 80 nm with concentrations about 50 to 500 ppm. Addition of metal oxide nanoparticles to biodiesel can improve brake thermal efficiency, reduce brake specific fuel consumption, carbon monoxide (CO), unburned hydrocarbons (HC), nitrogen oxide (NOx) and improve carbon dioxide (CO2) emission due to the catalytic effect of metal oxide nanoparticles. Metal oxide acts as an oxidation catalyst thereby reduce the carbon combustion activation temperature and thus enhances hydrocarbon oxidation, promoting complete combustion. Nanoparticles that are often used in various studies are nickel (II) oxide (NiO), cerium (IV) oxide (CeO2), titanium oxide (TiO2), zinc oxide (ZnO), aluminum oxide (Al2O3), and silicon dioxide (SiO2). This review paper describes the progress and development of nano metal oxide applications as additives for biodiesel, and the discussion in this paper is divided into 3 main topics, including the effects of nanoparticles on the properties of biodiesel, engine performance, and emission characteristics.